Implementasi Penilaian Sikap Berdasarkan Kurikulum 2013 Untuk Membentuk Karakter Siswa Di SekolahMenengah Pertama - PURWANTO, PURWANTO (2016)
Purwanto. S200130007. The Implementation of Attitude Assesment Based On 2013 Curriculum To Build The Junior High School Students' Characters. Master of Language Studies. Tesis. the Graduate School. University of Muhammadiyah Surakarta. 2016. This research aims to describe the plan and implementation value of attitude assessment based on 2013 curriculum to build junior high school students' personality characters. This research is based on qualitative investigation and it is using descriptive method throughout the whole research. The objects of the research are the planning and the execution of attitude assessment's implementation together with the effect towards the students' character building. The data collection on the research is passed on through three steps; they are documentation, observation, and interview. The Indonesian teachers of State Junior High School 2 Gondangrejo and State Junior High School 1 Mojogedang are planning the attitude assessment based on 2013 curriculum which is put in Learning Execution Plan (RPP) through the instruments and assessment rubrics as the teacher's observation, peer group assessment, and self assessment. The completion of the attitude assessment in State Junior High School 2 Gondangrejo is done by the teachers with the average score of spiritual attitude value of 3,10 (good), and responsible attitude value of 3,16 (good). The assessment in State Junior High School 1 Mojogedang with the average score of spiritual attitude value of 3,33 (good), decent attitude value of 3,33 (good). The spiritual attitude or the social attitude from both of schools is confirmed to be good based on the value of conversion score gain predicate of B (good). The attitude assessment gives effect on the students' behavior that they expressing the values of decent attitude towards their teachers and friends then their behavior will be rated. This attitude becomes the daily custom that it lingers inside the students' minds and that builds up their characters.